TINGKAT KEPUASAN PENGUNJUNG DI OBJEK WISATA DANAU LINOW LAHENDONG KOTA TOMOHON PROPINSI SULAWESI UTARA (Visitor Satisfaction In Linow Lahendong Tourist Object, Tomohon City North Sulawesi Province) - Niki Mamesah; Vicky R. B. Moniaga; Lyndon R. J. Pangemanan (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
This research was conducted for three months with a total ofÂ  30 respondents. The objective of this research isÂ  to assess the level of satisfaction of visitors to tourist attractions. South Tomohon Sub District, Minasaha Regency. The method used in obtaining the sample in this study was the Accidental Sampling technique, namely direct interviews with respondents using a questionnaire. The method of data analysis in this research uses descriptive method with a scale of measuring attitudes using a Likert scale. The research results showed that the satisfaction level of visitors to the Lake Linow Lahendong tourism motorcycle taxi in Tomohon City was at 57.92% which belongs to the Satisfied category. Â